Implementation of Class-Based Management in The Learning Process - Moh Masnun (Ilmu Inovasi Nusantara, 2023)
This research is grounded by the learning outcomes of grade III students are lacking and there needs to be more guidance, there are still students who are not fluent in reading, and there are still students who need to be guided by their parents during the learning process. So there is a need for research that aims to see the impact of classroom management in improving student learning outcomes. The objectives of this study are: 1) to determine the implementation of class management in class III MIN 8 Cirebon. 2) To find out the results of the implementation of class management towards improving student learning outcomes in class III MIN 8 Cirebon. 3) To find out what are the factors that affect the implementation of management in class III MIN 8 Cirebon. This research applies a qualitative approach. Theresearch method chosen is descriptive analytics, this research was carried out at MIN 8 Cirebon. Method information collection using observation, interviews, and documentation. Based on the results of good classroom management research proven effective in improving student learning outcomes, this is evidenced through the average score of grade III MIN 8 Cirebon students who have increased from before implementing class management well (pre-cycle) which showed a percentage of 65.15% and after implementing class management well which showed a percentage figure of 72.72%. Where the percentage figure of 72.72% is included in the percentage result. The effectiveness of the implementation of good classroom management on learning outcomes based on the category of the teacher's ability to manage the classroom